Targeted system approach to ethylene biosynthesis and signaling of a heat tolerant tomato cultivar; the impact of growing season on fruit ripening - Nguyen, Thao Minh Viet; Hertog, Maarten L. A. T. M.; Van de Poel, Bram; Tran, Dinh Thi; Nicolaï, Bart (Frontiers in Plant Science, 2023)
Growing tomato in hot weather conditions is challenging for fruit production and yield. Tomato cv. Savior is a heat-tolerant cultivar which can be grown during both the Vietnamese winter (mild condition) and summer (hot condition) season. Understanding the mechanisms of ethylene biosynthesis and signaling are important for agriculture, as manipulation of these pathways can lead to improvements in crop yield, stress tolerance, and fruit ripening. The objective of this study was to investigate an overview of ethylene biosynthesis and signaling from target genes to proteins and metabolites and the impact of growing season on a heat tolerant tomato cultivar throughout fruit ripening and postharvest storage. This work also showed the feasibility of absolute protein quantification of ethylene biosynthesis enzymes. Summer fruit showed the delayed peak of ethylene production until the red ripe stage. The difference in postharvest ethylene production between winter and summer fruit appears to be regulated by the difference in accumulation of 1-aminocyclopropane-1-carboxylic acid (ACC) which depends on the putative up-regulation of SAM levels. The lack of differences in protein concentrations between winter and summer fruit indicate that heat stress did not alter the ethylene biosynthesis-related protein abundance in heat tolerant cultivar. The analysis results of enzymatic activity and proteomics showed that in both winter and summer fruit, the majority of ACO activity could be mainly contributed to the abundance of ACO5 and ACO6 isoforms, rather than ACO1. Likewise, ethylene signal transduction was largely controlled by the abundance of ethylene receptors ETR1, ETR3, ETR6, and ETR7 together with the constitute triple response regulator CTR1 for both winter and summer grown tomatoes. Altogether our results indicate that in the heat tolerant tomato cv. Savior, growing season mainly affects the ethylene biosynthesis pathway and leaves the signaling pathway relatively unaffected.